Displacement of fractured root canal instrument in the space of floor of mouth - Wojciech Świątkowski; Mansur Rahnama; Katarzyna Wieczorek; Izabela Jastrzębska-Jamrogiewicz; Rafał Jamrogiewicz (Kazimierz Wielki University, 2018)
The aim of study was to describe the case of displaced endodontic file. Endodontic treatment is one of the most precise and at the same time the most difficult areas of dentistry. This implies that it is bound with a number of complications.The occurrence of complications of root canal treatment, one of which is displacement of endodontic instruments in the surrounding tissue, requires accurate diagnosis - clinical and as well radiological examination. The instrument position in the soft tissues may cause displacement of the tool and damage to important anatomical structures. Surgical treatment must be precise so as removal of foreign body does not result in any iatrogenic complications.